2013
DOI: 10.1007/s11250-013-0398-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of prepartum serum metabolites for incidence of clinical and subclinical mastitis in grazing primiparous Holstein cows

Abstract: The aim of this study was to measure changes in biochemical markers in the peripartum period of primiparous Holstein cows diagnosed with subclinical and clinical mastitis. In this study, 37 dairy cows were monitored daily during milking until 60 days postpartum and were categorized according to the occurrence of clinical mastitis (group mastitis (GM), n = 9) or subclinical mastitis (group subclinical mastitis (GSUB), n = 10) or absence of symptoms (control group (CG), n = 18). Blood samples were collected week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
9
0
1
Order By: Relevance
“…Furthermore, cows that develop clinical mastitis postpartum have been shown to have decreased glucose and increased NEFA and BHB concentrations prepartum (Moyes et al, 2009;Schwegler et al, 2013), which indicates a decreased DMI%BW and EB prepartum; however, to our knowledge, this is the first time that prepartum DMI%BW and EB were compared between cows that did and did not develop clinical mastitis. Previous research has shown that hyperketonemia impairs phagocytic, chemotactic, and killing ability of neutrophils and that immunosuppression peripartum is a predisposing factor for mastitis postpartum (Suriyasathaporn et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, cows that develop clinical mastitis postpartum have been shown to have decreased glucose and increased NEFA and BHB concentrations prepartum (Moyes et al, 2009;Schwegler et al, 2013), which indicates a decreased DMI%BW and EB prepartum; however, to our knowledge, this is the first time that prepartum DMI%BW and EB were compared between cows that did and did not develop clinical mastitis. Previous research has shown that hyperketonemia impairs phagocytic, chemotactic, and killing ability of neutrophils and that immunosuppression peripartum is a predisposing factor for mastitis postpartum (Suriyasathaporn et al, 1999).…”
Section: Discussionmentioning
confidence: 90%
“…This is in agreement with the results from Hammon et al (2006), who showed that the killing ability of neutrophils was negatively correlated with NEFA concentrations in the week of calving. In addition, clinical mastitis postpartum has been linked to decreased glucose and increased NEFA and BHB concentrations prepartum (Jánosi et al, 2003;Moyes et al, 2009;Schwegler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Long-chain fatty acids (LCFA) are increased in the plasma in cows around partum, a time where these animals are more susceptible to acquiring infectious diseases, and an association between LCFA and infectious disease incidence has been suggested. 6,7 In bovine neutrophils, the unsaturated fatty acids oleic (OLA) and linoleic (LA) acid increase ROS production, matrix metalloproteinase (MMP)-9 release, and cyclooxygenase (COX)-2 and IL-8 mRNA levels. [8][9][10] OLA and LA-induced ROS and MMP-9 release are mediated through free fatty acid receptor-1 (FFAR1/ GPR40).…”
Section: Introductionmentioning
confidence: 99%
“…These changes were not reported between control and the diseased cows at post-fresh period. Some other literature reports revealed that glucose concentration is reduced and NEFA concentration is increased during the prepartum period in primiparous cows that developed clinical mastitis in the postpartum period compared to healthy cows (Schwegler et al, 2013). Moyes et al (2009) observed that a higher prepartum glucose concentration is associated with the occurrence of postpartum diseases.…”
Section: Discussionmentioning
confidence: 93%
“…Elevated NEFA concentration in plasma is a prerequisite for development of hepatic lipidosis that occurs in DA cows (Rehage et al, 1996). Schwegler et al (2013) reported a reduced serum glucose concentration and increased serum NEFA concentration during the prepartum period in primiparous cows that developed clinical mastitis in the postpartum period compared to healthy cows. Cameron et al (1998) stated that NEB is expected in milking cows, so blood NEFA levels are high after calving and can be hardly evaluated.…”
Section: Discussionmentioning
confidence: 96%